Exercise and Physical Activity eHealth in COVID-19 Pandemic: A Cross-Sectional Study of Effects on Motivations, Behavior Change Mechanisms, and Behavior - Marchant, Gonzalo; Bonaiuto, Flavia; Bonaiuto, Marino; Guillet Descas, Emma (Frontiers in Psychology, 2021)
Objectives: The aims of this research were: (1) to compare the levels of physical activity of eHealth users and non-users, (2) to determine the effects of these technologies on motivations, and (3) to establish the relationship that could exist between psychological constructs and physical activity behaviours. Methods: This cross-sectional study involved 569 adults who responded to an online questionnaire during confinement in France. The questions assessed demographics, usage of eHealth for exercise and physical activity and behavioural levels. Also, the questionnaire measured the constructs of Socio-Cognitive theory, the Theory of Planned Behaviour and Automaticity facets towards eHealth for exercise and physical activity. Results: Participants who were users of eHealth for exercise and physical activity presented significantly higher levels of vigorous physical activity and total physical activity per week than non-users (p < .001). Chi-square test showed significant interactions between psychological constructs towards eHealth (i.e., self-efficacy, behavioural attitudes, intentions and automaticity) and physical activity levels (all interactions were p < .05). Self-efficacy was significantly and negatively correlated with walking time per week. Concerning the automaticity facets, efficiency was positive and significantly correlated with vigorous physical activity levels per week (p < .05). Then, regressions analyses showed that self-efficacy and automaticity efficiency explained 5% of the variance of walking minutes per week (ß = -.27, p < .01) and vigorous physical activity per week (ß = .20, p < .05), respectively. Conclusions: This study has shown that people during confinement looked for ways to stay active through eHealth. However, we must put any technological solution into perspective. The eHealth offers possibilities to stay active, but its benefits and the psychological mechanisms that affect them remain to be demonstrated: eHealth could be adapted to each person and context.